Getting to Know the Inner Self. Exploratory Study of Identity Oriented Psychotrauma Therapy—Experiences and Value From Multiple Perspectives - Stjernswärd, Sigrid (Frontiers in Psychiatry, 2021)
Early trauma and failures in attachment attunement can affect future relational patterns, health and well-being. The processing of trauma, especially complex trauma, through adequate interventions may help integrate traumatic experiences, enhance health and quality of life. Despite years of clinical practice with Identity oriented psychotrauma therapy (IoPT), there is a lack of scientific research on the subject. Objective: The study’s aim was to explore the experiences and value of IoPT for persons with experiences of IoPT, whether as a therapist, client, representative and/or observer. Methods: The study has an explorative, qualitative design. Data collection through individual in-depth interviews and focus groups with 20 participants and data analysis were inspired by grounded theory. Results: The results showed an exploratory process of self-discovery and self-development, Getting to know the inner self, to which all categories were interrelated through their contribution to the process. The findings shed light on the experiences and tangible value of IoPT for the participants from the perspectives of client, therapist, representative and observer. These perspectives were intertwined and illuminated in terms of their contribution to the process. Conclusion: IoPT seems to have transformative potential in terms of a self-exploratory journey from multiple perspectives. The need for effective treatments to enhance health and prevent further ill health in persons affected by complex trauma motivates the exploration of novel treatment approaches and formats to support clients towards health enhancing strategies. Further quantitative and qualitative research is motivated to enhance our understanding of the workings and value of IoPT for self-development, health and quality of life.